Utilization of Ex Tin Mine Lake For Aquaculture: Case Study Of Muntok Sub District, West Bangka Regency - Ira Triswiyana; Ayu Permatasari; Ardiansyah Kurniawan (Faculty of Science and Technology University Ibrahimy, 2019)
Tin mining has left hundreds of ex-mine lake in Muntok Subdistrict, West Bangka Regency, which is both problems and potential to be exploited. Empowerment of the lake for freshwater fish farming can provide alternative livelihood opportunities besides tin mining. The study of the use of the lakes for fish farming aims to determine the purpose of fish farming with its problems and potential. The study was conducted in June - July 2018 with a descriptive qualitative method through a process of interviews and observations during the implementation of the task of fisheries instructor. The object is on three groups who use the lake for fish farming. The lake can be used productively for catfish and catfish culture utilizing the system of the pen culture. The obstacle of using the lake for fish culture is the potential for bioaccumulation of heavy metals, the difficulty of implementing water quality management, and lower productivity compared to artificial ponds. Under cultivation is recommended to choose Clarias commodities in consideration of consumer safety against bioaccumulation of heavy metals.